The role of the proteasomal ATPases and activator monoubiquitylation in regulating Gal4 binding to promoters - Ferdous, Anwarul (Cold Spring Harbor Laboratory Press, 2007)
Recent studies have shown that the intersection between transcription and proteins involved in the ubiquitin–proteasome pathway encompasses both proteolytic and nonproteolytic functions. Examples of the latter type include evidence that monoubiquitylation of some transcriptional activators stimulates their activity. In addition, the proteasomal ATPases are recruited to many active promoters through binding to activators and play an important, nonproteolytic role in promoter escape and elongation. In this study, we report the discovery of a new nonproteolytic activity of the proteasome (specifically the proteasomal ATPases): the active destabilization of activator–promoter complexes. This reaction depends on the presence of an activation domain and ATP. Destabilization is inhibited in vitro and in vivo if the protein is monoubiquitylated or if ubiquitin is genetically fused to the activator. The fact that monoubiquitylated activator is resistant to the “stripping” activity of the proteasomal ATPases may explain, in part, why some activators require this modification in order to function efficiently.